Implementasi Akad Rahn di Pegadaian Syari'ah Untuk Meningkatkan Kesadaran Tentang Keuangan Syari'ah - Muhammad Wifqi Hidayatullah; Putri Indah Lestari; Hawa Azzah Fauziah; Kirana Mahardhika Rahma; Muhammad Taufiq Abadi (CV. ALIM'SPUBLISHING, 2024)
A sharia financial institution is an entity whose activities in the field of sharia finance and whose assets are based on sharia principles, both in financial and other matters. One of the sharia financial institutions in Indonesia is Pegadaian Syariah (Rahn). Rahn is an agreement to hand over goods as collateral for a debt, which allows the person concerned to borrow money. The implementation carried out by sharia pawnshops includes efforts to foster sharia financial literacy in the community, which will later be able to help the family economy and give rise to new businesses when people understand and know about sharia pawnshops. Due to the lack of public interest in sharia finance, especially sharia pawnshops, the aim of this research is to communicate the concept of pawning in classical jurisprudence literature, the implementation of Rahn contracts in sharia pawnshops and ways to increase public interest in sharia financial institutions, especially sharia pawnshops. The aim of this research is to inform the public about the concept of pawning, especially sharia pawnshops